DETERMINASI UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP PENGHINDARAN PAJAK - Fitriya Diah Pramesthi; Witono, Banu (JURNAL ILMIAH EDUNOMIKA, 2025)
Indonesia as a developing country relies heavily on tax revenue to support the state budget. Tax avoidance practices, including through increasing corporate debt (thin capitalization), cost the state hundreds of billions of rupiah every year. For example, around 40% of palm oil companies are suspected of not paying taxes according to regulations. Although the size of palm oil plantations has increased, tax revenues have declined. Government efforts such as the 2016 tax amnesty program aim to address tax violations, but also show recognition of corporate non-compliance. Tax avoidance is often done with planning that remains legal but reduces tax liabilities. One method of measuring this practice is CETR (Cash Effective Tax Rate). A low CETR value indicates high tax avoidance. With policy improvements and increased compliance, Indonesia's tax revenue is expected to increase significantly. This study aims to analyze company size, profitability, leverage, liquidity on tax avoidance. The object of this research is banking companies listed on the IDX for the period 2021-2023 with a sample of 35 companies. The method used in this research is quantitative research method in the form of causative. The results showed that company size and profitability have an effect on tax avoidance, while leverage and liquidity have no effect on tax avoidance.